Antitrest Legislation of the USA 1913–1915 - R. T. Mardaliev (Теоретическая и прикладная юриспруденция)
The article discusses the process of creating social legislation in the United States of America at the beginning of the 20th century. This legislation in the country was created later than in European countries. It was issued during the presidency of Woodrow Wilson. The process of reviewing these bills in the US Congress, as well as the political struggle associated with their development and adoption, the analysis of the documents themselves are the focus of this article.